Philosophical and Formal Approaches to Linguistic Analysis. - Stalmaszczyk, Piotr (De Gruyter, 2012)
Articles gathered in the volume focus on traditional and contemporary debates within the philosophy of language, and on the interfaces between linguistics, philosophy, and logic. The topics of individual contributions cover such diverse issues as analytic accounts of the a priori and implicit definitions, medieval and contemporary theories of fallacy, game-theoretical semantics, modal games in natural language and literary semantics, possible-world theories and paradoxes involving structured propositions, extensions to Dynamic Syntax, semantics of proper names, judgement-dependence, tacit know.